Uma proposta de sequência didática para o ensino de equação do 1º grau - Santos, Franciscleide Ribeiro dos (2024)
The present work aims to promote the connection between problem-solving involving firstdegree equations and the daily lives of 7th-grade students in a public school in Bahia. To achieve this goal, a didactic sequence based on the assumptions of Brousseau's Theory of Didactic Situations was adopted, which emphasizes the construction of mathematical knowledge through the interaction between the student and their environment. The methodology included a combination of diverse activities, such as historical research on equations, reading and interpreting texts, formulating and solving contextualized problems, culminating in the experimentation and construction of physical balance models. These practical activities were designed to facilitate the understanding of the concept of first-degree equations by relating it to the students' real-life experiences. The implementation of this didactic sequence revealed a significant increase in students' interest in understanding first-degree equations, especially when the activities diverged from traditional teaching methods, which are often focused on memorization and mechanical repetition of procedures. The methodological approach of this study was inspired by the stages of Didactic Engineering, with a special emphasis on the experimentation and validation of mathematical concepts through concrete practices. This process not only encouraged active student participation but also promoted an environment of knowledge exchange, where dialogue and collaboration were central to the construction of mathematical understanding. Thus, this work contributes to improving the teaching of first-degree equations, demonstrating the effectiveness of pedagogical practices that contextualize and bring mathematical content closer to students' lived experiences.